2014
DOI: 10.1017/s1751731114000172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free thymol on differential gene expression in gastric mucosa of the young pig

Abstract: Thymol is the most common molecule in thyme and has been proposed as an oral alternative to antibiotics in the feed of pigs and broilers. The knowledge of the in vivo physiological effects of thymol on tissues is limited, particularly its impact on the gastric mucosa, where it is primarily absorbed when it is orally supplied. In this study, thymol (TH, 50 mg/ kg BW) or a placebo (CO) was introduced directly into the stomach of 8 weaned pigs that were slaughtered 12 h later and sampled for gastric oxyntic and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…Thymol (0–2 mM) exerted its relaxant effect on smooth muscle cells by opposing Ca 2+ activation and ATP dependent process by its potent anti-spasmodic effect (Tamura and Iwamoto, 2004). Thymol (50 mg/kg) was shown to influence gastric maturation and function via stimulation of gastric proliferative activity and the control of digestive activity in weaned pigs (Colombo et al, 2014). …”
Section: Thymol In Gastrointestinal Disordersmentioning
confidence: 99%
“…Thymol (0–2 mM) exerted its relaxant effect on smooth muscle cells by opposing Ca 2+ activation and ATP dependent process by its potent anti-spasmodic effect (Tamura and Iwamoto, 2004). Thymol (50 mg/kg) was shown to influence gastric maturation and function via stimulation of gastric proliferative activity and the control of digestive activity in weaned pigs (Colombo et al, 2014). …”
Section: Thymol In Gastrointestinal Disordersmentioning
confidence: 99%
“…cinnamaldehyde (cinnamon), 132,133 allicin and diallyl disulfide (garlic, onion), AITC (horseradish, mustard, wasabi), carvacrol (oregano, marjoram), eugenol (cloves), oleocanthol (olive oil), methyl salicylate (wintergreen), gingerol (ginger), D 9 -tetrahydrocannabinol (marijuana-derived psychoactive compound) and thymol (thyme). 18,[134][135][136] Thiols react with dialkyl disulfide-S-oxides and dialkyl disulfides to give mixed disulfides. 137 As can be seen in Figure 7, it is probable that a cysteine thiol of TRPA1 might react with allicin and diallyl disulfide to yield the same Sallyl product.…”
Section: Exogenous Military and Law-enforcement Compoundsmentioning
confidence: 99%
“…However, failure to explore the potential value of TRPA1 antagonists against agents such as chlorine gas may be a potentially missed opportunity (though it should be noted that the pig is conspicuous by the paucity of papers on its use as a model in TRPA1 studies). Colombo et al 136 have reported that thymol activates the TRPA1 gene in pig pyloric and oxyntic mucosa, whereas it downregulates genes associated with other TRP channels. Boudry and Perrier 244 also reported that ion secretion in the small intestine of the pig is increased by TRPA1 activators such as cinnamon and thyme.…”
Section: Endogenous Trpa1 Agonistsmentioning
confidence: 99%
“…Finally, thyme is used as a phytogenic feed additive on the basis of the antibacterial activity of its essential oils (mainly thymol). However, it is also considered to stimulate physiological processes in the pig (Colombo et al 2014). As the presumed bioactive ingredient in thyme is an essential oil, watery extracts may contain only very low amounts and therefore low bioactivity was expected.…”
Section: E Coli Adhesion Assays To Ipec-j2 Cells and Subsequent Infementioning
confidence: 99%
“…A final experiment was conducted to examine the hypothesis that cell cultures may need a preincubation for the feed additives to act. In vivo, feed additives could be present before pathogenic E. coli reach the intestine and thus, the physiology of small intestinal epithelial cells may have been modified as shown by Colombo et al (2014) for thymol. However, a 24 h preincubation with the tested feed additives did not change the outcome.…”
Section: E Coli Adhesion Assays To Ipec-j2 Cells and Subsequent Infementioning
confidence: 99%